2013
DOI: 10.1007/s10986-013-9204-x
|View full text |Cite
|
Sign up to set email alerts
|

Extinction times for a birth–death process with weak competition

Abstract: We consider a birth-death process with the birth rates iλ and death rates iµ + i(i − 1)θ, where i is the current state of the process. A positive competition rate θ is assumed to be small. In the supercritical case when λ > µ this process can be viewed as a demographic model for a population with a high carrying capacity around λ−µ θ . The article reports in a self-contained manner on the asymptotic properties of the time to extinction for this logistic branching process as θ → 0. All three reproduction regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…For both regimes, Nåsell (2011) poses as an open problem the determination of the mean extinction time E T N . Our results have some similarity with Theorem 2(ii) of Sagitov and Shaimerdenova (2013), who study the distribution of the extinction time for a different version of the logistic model in a completely different limit. Barbour, Hamza, Kaspi and Klebaner (2015) study a very general class of population models, which includes this one.…”
supporting
confidence: 84%
“…For both regimes, Nåsell (2011) poses as an open problem the determination of the mean extinction time E T N . Our results have some similarity with Theorem 2(ii) of Sagitov and Shaimerdenova (2013), who study the distribution of the extinction time for a different version of the logistic model in a completely different limit. Barbour, Hamza, Kaspi and Klebaner (2015) study a very general class of population models, which includes this one.…”
supporting
confidence: 84%
“…We are aware of only a few mathematical results related to our work. In [9], the authors do not study the quasi-stationary distribution but only the mean time to expectation starting from a state of order K for which they obtain the asymptotic behavior in K (see also [21]). Here we are able to control this quantity for all initial states and also for the quasi-stationary distribution as a starting distribution.…”
mentioning
confidence: 99%
“…The selection of these was based on the mathematical results of Sagitov and Shaimerdenova (2013) on the non‐spatial stochastic logistic model, thus corresponding to our case of ε=0. Denoting by MTE the mean time to extinction, Sagitov and Shaimerdenova (2013) showed that the log(MTE) increases linearly with log(U) for the critical value of m=mc, whereas log(MTE) increases sublinearly with log(U) for m>mc and superlinearly with log(U) for m<mc. This behaviour is illustrated in Figure 2, where we have simulated the model with different domain sizes, for values of the parameter m that are both just below and just above the critical value of mc=A+.…”
Section: Methodsmentioning
confidence: 99%